2012
DOI: 10.1080/08870446.2010.542814
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of psychosocial distress in breast cancer: Prevalence and risk factors

Abstract: This longitudinal study was conducted among 102 women with non-metastasic breast cancer to identify the time evolution and prevalence of distress at specific times through diagnosis and treatment of disease: preliminary diagnosis, surgery, definitive diagnosis and chemotherapy. Additionally, the study aimed to examine the role of demographic, medical and psychosocial factors on distress. The results indicated that prevalence of distress was higher at initial diagnosis (25%) than the following time points (appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
4
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 33 publications
5
125
4
18
Order By: Relevance
“…Another report indicated that psychosocial distress experienced within the first year post diagnosis has a huge impact on psychosocial wellbeing and quality of life in long term BC survivors (Mehnert and Koch, 2008). Andreu and colleagues revealed in a study of 102 BC survivors that psychological factors such as emotional suppression, strategies for coping with treatment and gaining social support from community and family were conducive to improved psychological status (Andreu et al, 2012). Thewes and colleagues investigated psychological distress in pre and post-menopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…Another report indicated that psychosocial distress experienced within the first year post diagnosis has a huge impact on psychosocial wellbeing and quality of life in long term BC survivors (Mehnert and Koch, 2008). Andreu and colleagues revealed in a study of 102 BC survivors that psychological factors such as emotional suppression, strategies for coping with treatment and gaining social support from community and family were conducive to improved psychological status (Andreu et al, 2012). Thewes and colleagues investigated psychological distress in pre and post-menopausal women.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies found that emotion suppression or dampening (as measured by the CECS) was not significantly related to psychological distress, autonomic physiology, or survival Giese-Davis et al, 2008;Goodwin et al, 2004;Nakatani et al, 2014;Watson et al, 1999).Emotional dampening, as measured by the WCQ, was associated with longer survival times (Andreu et al, 2012;Classen et al, 1996;Reynolds et al, 2000;Schlatter et al, 2010;Tamagawa et al, 2013).…”
Section: Dimensions Of Emotional Regulation Found In the Included Stumentioning
confidence: 96%
“…A majority of studies have used the CECS as an overall scale to measure "control of emotions" or "suppression of emotions". It has been the most common scale used to evaluate emotion control in the context of breast cancer and presented good internal consistency with α's ranging from .83 to .95 Andreu et al, 2012;Cameron et al, 2007;Classen et al, 1996;Giese-Davis et al, 2002, 2006bIwamistu et al, 2003Iwamistu et al, , 2005aIwamistu et al, , 2005bSchlatter et al, 2010) and reliability with 3-4 month testretest reliability = .95 . The CECS has been used with a wide variety of populations (see Table 1 for data on the number of publications describing the use of the CECS and all the measures reviewed) and has shown similar levels of reliability.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…El DT (≥5) detectó un 94% de los casos positivos (Se) y un 48% de los casos negativos (Sp). Estos resultados, similares a los previamente encontrados en pacientes oncológicos españoles (1), confirman el adecuado comportamiento del DT para descartar los no casos (screening) en pacientes con neoplasias hematológicas. No obstante, los datos respecto a sus niveles de especificidad, VPP e IU+ indican que necesita ser mejorado en lo que a "identificación de caso" se refiere (18)(19) .…”
Section: Discusión / Conclusionesunclassified
“…Los estudios sobre prevalencia del distrés en cáncer revelan que aproximadamente tres de cada diez pacientes oncoló-gicos tiene niveles significativos de distrés a lo largo del proceso de la enfermedad (1)(2)(3)(4)(5) . Asimismo, un extenso meta-análisis reciente (6) muestra que los trastornos emocionales están presentes en un 30-40% de los pacientes oncológicos.…”
Section: Introductionunclassified